Enhanced photothermal therapy for oral cancer using benzothiadiazole-based nanoparticle-loaded hydrogels - Zi Fu; Ling Huang; Xinyu Zhang; Zhichao Zheng; Lihong Wu; Huade Zheng (Artificial Cells, Nanomedicine, and Biotechnology, 2025)
Recent advances in photothermal therapy (PTT) using nanoparticles (NPs), particularly benzothiadiazole-based agents, offer promising strategies for targeted cancer treatment with enhanced efficacy and reduced side effects. However, challenges such as poor stability and limited retention at the tumour site persist, necessitating the development of advanced delivery systems to optimize the effectiveness of these NPs in clinical applications. In this study, we synthesized a benzothiadiazole-based photothermal small molecule, BPD-BBTD NPs, with a median particle size of 116 nm. And subsequently incorporated them into a chitosan (CS) and hydroxyethyl cellulose (HEC) matrix to form a novel hydrogel, BPD-BBTD NPs @CS-HEC. The photothermal efficacy of both the NPs and the hydrogel against oral squamous cell carcinoma (OSCC) was further explored. The photothermal conversion efficiency of BPD BBTD NPs small molecules can reach 40%. When the concentration is 400 μg/mL, the temperature can reach 75 °C after 3 min of NIR irradiation. The hydrogel’s dense network structure was designed to effectively retain heat within its matrix, thus enhancing the photothermal effect and reducing heat dissipation. Our in vitro experiments demonstrated that BPD-BBTD NPs significantly inhibited the proliferation and migration of OSCC cells while exerting minimal cytotoxic effects on normal cells. The survival rates of mouse fibroblasts (L929) and human oral keratinocytes (Hok) were over 80%. Mechanistic investigations indicated that under near-infra-red (NIR) light irradiation, the NPs increased the production of reactive oxygen species (ROS) in OSCC cells. This ROS upregulation further led to apoptosis in OSCC cells, primarily through the reduction of mitochondrial membrane potential, a consequence of heat stress induced by NIR irradiation. Furthermore, the anti-tumour efficacy of BPD-BBTD NPs @CS-HEC hydrogel was validated using an in situ mouse model of OSCC. Furthermore, the relative change rate of tumour volume before and after treatment was reduced by 94.4%. In conclusion, our findings suggest that BPD-BBTD NPs @CS-HEC hydrogels, under the activation of NIR light, represent a promising biomaterial for the targeted treatment of OSCC, offering a synergistic approach by combining PTT with localized, sustained treatment delivery.